The meaning of effect tax culture in movement of government - Burnasheva, V. R. (Journal of Economic Research & Business Administration, 2015)
At different times, taxes, as part of government policy, largely infl uenced the sustainable development of society. Tax state activity involves organizing taxation and ensure its implementation in order to meet its cash requirements. In the development of the patriotic duty of the taxpayer plays an important role shaping the tax culture. In this regard, the tax state activity in the framework of tax policy should include the use of tools aimed at creating a high payment behavior of taxpayers. Tax culture – is a human activity that is manifested in the form of self-expression and self-knowledge of the taxation system of the state. Tax culture forms in taxpayer certain behavior with the characteristic thoughts, rendering it thus, managerial impact. Major factor of effective tax activity of the state is the tax culture, the increasing of its level, it will promote improvement of tax system of Kazakhstan.